The Advance of African Capital : The Growth of Nigerian Private Enterprise. - Forrest, Tom (International African library., 1994)
Combining ethnographic and historical perspectives, this study is the most detailed, most extensive account of medium- and large-scale African business. Not only a valuable digest of business activities, this important study also challenges existing views about African enterprise and is highly relevant to policy-makers concerned with economic development.